Study on Disease Mechanism and Theoretical Quantification Method of Tunnel Structure - Yu Liu; Chun-an Tang; Peng-yu Wang; Yong-ping Guan; Shu-hong Wang (Advances in Civil Engineering)
Most tunnel structures tend to have different degrees of structural damage such as leakage, concrete cracking, lining salinization, and falling blocks after the operation for a period. Compared with the diversity of tunnel disease detection methods, there are few studies on the methods of quantifying and evaluating the main structural diseases of the lining. Based on the regular inspection data of expressway tunnels in Liaoning Province, this paper summarizes the distribution characteristics and laws of existing structural defects of tunnel lining. In addition, based on the in-depth study of the main structural diseases of the tunnel, the extenics theory is used to extract, quantify and classify several indicators that can accurately reflect the health status of the structure, and then establish the corresponding matter-element model to determine the weight of each indicator and the tunnel structure. The comprehensive correlation degree of disease grades is combined with the qualitative evaluation and quantitative research of lining structure diseases to construct a health evaluation system for tunnel lining structures, which is convenient for managers to make reasonable decisions. At the same time, combined with the actual test data of tunnel engineering, the calculation and analysis of the extension model are carried out to verify the engineering applicability of the model.